10대 미혼모의 문제와 복지대책에 관한 연구 - 도미향; 정은미 (청소년복지연구, 3(2), 2001)
This study is to propose future welfare policies through a survey on current grovemment welfare policies and the problems and caused of unwed teen age mothers. This study was executed through analysis of previous theoretical and experimental research and statistics. First is a rationalization of future welfare policies and systems which are financially supported by the govemment, laws for unwed mothers, legalization on the responsibility of unwed fathers, continuous development, application, and evaluation of program, and systematization of statistical data. Second, in order to improve sex education and unwed mother programs the following suggestions are needed for the prevention of unwed mothers: sex education on line, substantial sex education through various small groups, diversification and improvement of management of counseling centers and residential treatment homes for unwed mothers, diversification and specialization of counseling approach for unwed parents and their family, and technical job training programs in community. KCI Citation Count: 8